2016
DOI: 10.1093/ofid/ofw072
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Intravenous Catheter Placement Is an Underrecognized Source of Staphylococcus aureus Bloodstream Infection

Abstract: Few studies have focused on the risks of peripheral intravenous catheters (PIVs) as sources for Staphylococcus aureus bacteremia (SAB), a life-threatening complication. We identified 34 PIV-related infections (7.6%) in a cohort of 445 patients with SAB. Peripheral intravenous catheter-related SAB was associated with significantly longer bacteremia duration and thrombophlebitis at old PIV sites rather than current PIVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 12 publications
3
28
0
1
Order By: Relevance
“…However, some studies in Japan showed more frequent isolation of Candida spp. among PLABSI (8.1% to 14.7%) [15–19]. This result might reflect the difference in practice of using peripheral lines, not CVCs, to administer parenteral solutions in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies in Japan showed more frequent isolation of Candida spp. among PLABSI (8.1% to 14.7%) [15–19]. This result might reflect the difference in practice of using peripheral lines, not CVCs, to administer parenteral solutions in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of PLABSI secondary to Candida spp. is reported to range from 8.1% (5/62) to 14.7% (20/136) in Japan [15–19] and 0.2% to 1.1% in England [20]. Worldwide, there is a paucity of data on detailed clinical and epidemiological features of PLABSI, such as predictive factors.…”
Section: Introductionmentioning
confidence: 99%
“…The bloodstream infections were categorized as community onset (CO) if the initial culture was collected within 72 h of admission and hospital-onset (HO) if collected greater than 72 h after admission. Data on primary site of infection were collected (34). The primary site of infection was defined based on reported symptoms prior to bacteremia, coupled with diagnostic studies.…”
Section: Methodsmentioning
confidence: 99%
“…The most serious complication of PIVC placement is infection with Staphylococcus aureus bacteremia (SAB). PIVC‐related SAB represents as much as 25% of all health care–associated SAB episodes …”
mentioning
confidence: 99%